The Analysis of Office Infrastructure Facilities at Cv. X - Alfaaflahah, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to analyze office infrastructure facilities at CV. X company and find out its impact on employee comfort. Good office infrastructure facilities can support smooth operations to achieve goals. This research uses a qualitative descriptive approach, namely by describing and analyzing the problems found. This qualitative research is based on primary data and secondary data. Primary data is obtained through observation, interviews, and documentation, while secondary data is obtained from articles, books, and previous research relevant to the research topic. Based on the results of the research, office infrastructure facilities at CV. X is in good condition, but does not support employee comfort. Such as office space with desks that are not neatly arranged, poor lighting in the production room, and low employee awareness in maintaining environmental cleanliness. This research is important to provide insight into the importance of office infrastructure facilities in supporting comfort at work.